Asset management stewardship: The effectiveness of public-private mix governance structures - Mills, D.; Brown, Kerry; Waterhouse, J. (Institute of Electrical and Electronics Engineers ( IEEE ), 2008)
Major infrastructure assets are often governed by a mix of public and private organizations, each fulfilling a specific and separate role i.e. policy, ownership, operation or maintenance. However, it is increasingly problematic to maintain separate and distinct governance arrangements for each of these functions due to their criticality to achieving social outcomes such as supply of water, power and transport and their interdependency in terms of risk management. The success of long term asset management is therefore becoming reliant on coalitions of organizations and groups working in a co-coordinated and collaborative way to deliver services. Yet, it is unclear how to conceptualize these networks of relationships and to determine the types of entities and arrangements that will best contribute to successful collaborative governance. Stewardship theory is revisited to provide a lens through which asset management governance can be examined. It is argued that the concerns of the community in regard to the long-term sustainability of infrastructure assets from environmental, accountability, strategic and business perspectives may be well served by a renewed conceptualization of stewardship theory.